The subgenus Sinephemera Kluge, 2004 in China (Ephemeroptera: Ephemeridae: Ephemera Linnaeus, 1758) - Lei, Zhi-Ming; Zhou, Chang-Fa (Zootaxa, 2024)
China has the greatest diversity of species within the genus Ephemera Linnaeus, 1758. However, there has been no systematic revision of these species in recent decades, particularly concerning their nymphs. This study describes and photographs 13 Chinese species from the subgenus Sinephemera Kluge, 2004, including five new ones (E. bistria sp. nov., E. cornea sp. nov., E. obliqua sp. nov., E. rubera sp. nov., E. rubrogata sp. nov.) and confirms the presence of another in China (E. separigata Bae, 1995). The nymphal stage of E. purpurata Ulmer, 1919, which has asymmetrical mandibular tusks, is also described for the first time. A new synonymy is proposed: E. axillaris Navás, 1930 (= E. hsui Zhang et al., 1995, syn. nov.). Additionally, the synonymy of E. pictipennis Ulmer, 1919 with E. nigroptera Zhou et al., 1998, has been confirmed. The key characters and diagnoses of other four species (E. japonica McLanchlan, 1875, E. pictiventris McLanchlan, 1894, E. shengmi Hsu, 1937, E. strigata Eaton, 1892) and the single European species in the subgenus Sinephemera (E. glaucops Pictet, 1843) are provided too. Additionally, the imaginal and nymphal stages of these 14 species are reported. Morphologically, the longitudinal stripes on abdominal tergites and venation patterns in certain species (such as E. glaucops and E. shengmi) suggest that the subgenera Sinephemera and Ephemera s. str. can be differentiated primarily by the presence or absence of titillators. Moreover, species like E. bistria sp. nov., E. glaucops and E. shengmi have a relatively long first segment of their male forceps, which connect the genus Ephemera to other genera in the family Ephemeridae. Furthermore, the divided styliger plate, colorful body and wings of E. rubrogata sp. nov. and the median spines on tergites I–II of E. obliqua sp. nov. are found similar to the family Neoephemeridae. Both imaginal and nymphal keys to the 14 species are also provided.